2016
DOI: 10.1080/10962247.2016.1162226
|View full text |Cite
|
Sign up to set email alerts
|

Technology selection for infectious medical waste treatment using the analytic hierarchy process

Abstract: The overall objective of this paper was to evaluate five different technologies used for infectious medical waste treatment and select the optimum one by means of multicriteria analysis. Steam disinfection was selected as the optimum treatment technology, among others using incineration, microwave disinfection, chemical disinfection with sodium hypochlorite, and reverse polymerization with microwaves. The evaluation was based on four groups of criteria, specifically, environmental, economic, technical, and soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 14 publications
(19 reference statements)
0
41
0
Order By: Relevance
“…Autoclaves and microwaves operate using this technique [6,33]. Chemical processes where chemicals and disinfectants like sodium hypochlorite, sodium dioxide, peracetic acid or lime solution are react with the waste to destroy the constituent pathogens [6,34]. Biological processes: enzyme mixtures are used to decompose organic matters [4,6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Autoclaves and microwaves operate using this technique [6,33]. Chemical processes where chemicals and disinfectants like sodium hypochlorite, sodium dioxide, peracetic acid or lime solution are react with the waste to destroy the constituent pathogens [6,34]. Biological processes: enzyme mixtures are used to decompose organic matters [4,6].…”
Section: Discussionmentioning
confidence: 99%
“…Chemical processes where chemicals and disinfectants like sodium hypochlorite, sodium dioxide, peracetic acid or lime solution are react with the waste to destroy the constituent pathogens [6,34].…”
Section: Discussionmentioning
confidence: 99%
“…is defined using Eqs. (12) and (13). This reference preference relation represents the preference sequences of an optimal alternative:…”
Section: Id:p0350mentioning
confidence: 99%
“…A systematic and rigorous approach is required to effectively address this imperative issue. ID:p0085 A number of studies indicated the significance of the appropriate waste treatment technology selection [9,11,13]. The selection of appropriate waste treatment technology is considered to be a complex decision problem, which can be effectively handled by the methods of MCDM.…”
Section: Introductionmentioning
confidence: 99%
“…The choice of treatment technology is also important. For example, the proper treatment technology for cytostatic waste is incineration, whereas both incineration and disinfection can be used for infectious waste (Voudrias, 2016). Quantification of cytostatic waste generation is also important for health and safety reasons and for assessing their environmental impact, when they are released in the environment.…”
Section: Introductionmentioning
confidence: 99%